2018
DOI: 10.18203/2394-6040.ijcmph20180261
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors of non- communicable diseases among healthcare workers in Nelamangala: a cross sectional study

Abstract: Background: India is facing a new challenge of epidemiological health transition where the disease spectrum has changed from communicable diseases to non-communicable diseases. Diabetes mellitus, hypertension, stroke and cardiovascular diseases have emerged as major public health problems. Health care workers considered as mentors to general public are becoming victims to these life style disorders. Hence this study was conducted to assess the risk factors of non-communicable diseases among health care workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
1
6
1
Order By: Relevance
“…This prevalence is higher than the previous studies in India (9.20%), Iran (8.60%), and Ghana (16.07%) (Sahebi, Vahidi and Mousavi, 2010;Ahmed, Jadhav and Sobagaiah, 2018;Osei-yeboah et al, 2018). It could be possible due to that previous studies has included individual aged <30 years, excluded the individual with hypertension and diabetes, and different study settings; primary care center of rural areas (Sahebi, Vahidi and Mousavi, 2010;Ahmed, Jadhav and Sobagaiah, 2018;Oseiyeboah et al, 2018). Besides, one study had an annual health screening program for health workers, which could promote awareness among health care workers and led to a low prevalence of hypertension when comparing to this study (Osei-yeboah et al, 2018).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This prevalence is higher than the previous studies in India (9.20%), Iran (8.60%), and Ghana (16.07%) (Sahebi, Vahidi and Mousavi, 2010;Ahmed, Jadhav and Sobagaiah, 2018;Osei-yeboah et al, 2018). It could be possible due to that previous studies has included individual aged <30 years, excluded the individual with hypertension and diabetes, and different study settings; primary care center of rural areas (Sahebi, Vahidi and Mousavi, 2010;Ahmed, Jadhav and Sobagaiah, 2018;Oseiyeboah et al, 2018). Besides, one study had an annual health screening program for health workers, which could promote awareness among health care workers and led to a low prevalence of hypertension when comparing to this study (Osei-yeboah et al, 2018).…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies evident the momentous upsurge of hypertension and further cardiovascular disease risk factors in health workers in comparison to other working groups (Sumaila et al, 2016). Few studies show the prevalence of hypertension among health workers at 9.20% in India, 8.60% in Iran, and 35.27% in Thailand, respectively (Sahebi, Vahidi and Mousavi, 2010;Ahmed, Jadhav and Sobagaiah, 2018;Sirinara, Hanprathet and Jiamjarasrangsi, 2019). Nonetheless, until now, no studies have been conducted, which shows the direct figure of hypertension among health workers in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…However, our finding is supported by two other studies conducted among HCPs, one in Bangladesh 36 and another in India. 32 A comparison among the professional categories revealed that SSNs were more centrally obese than PHPs. This finding is also supported by two other studies, one from South Africa 37 and one from England, 38 which reported a higher burden of central obesity among nurses than other health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were in concordance with studies done in India. [ 5 10 13 14 ] On the contrary, studies done by Misra et al . in Assam and Kumar et al .…”
Section: Discussionmentioning
confidence: 98%